Initial oncological outcomes of nipple- and areola-sparing mastectomy in patients with breast cancer with nipple discharge - Hong Hou; Jing Xia; Lin Tan; Yue Yu; Xin Wang (World Journal of Surgical Oncology)
Abstract Objective This study aimed to assess the oncological safety of nipple- and areola-sparing mastectomy (NSM) compared to mastectomy without preservation of the nipple-areola complex (NAC) in patients with breast cancer presenting with nipple discharge. Methods Clinical data were retrospectively reviewed for 93 patients who underwent NSM and 133 patients who underwent mastectomy without NAC preservation for non-metastatic breast cancer between March 2015 and August 2023 at two hospitals. All patients presented with bloody or serous nipple discharge. Clinicopathological characteristics of both groups were assessed to evaluate the oncological safety of NSM and identify prognostic factors. Results Local recurrence rates and disease-free survival rates at 3 and 5 years did not differ significantly between the groups (p > 0.05). Univariate analysis identified tumor T stage, lymph node metastasis count, and histological grade as independent risk factors influencing disease-free survival and overall survival (p < 0.05). Tumors larger than 2 cm, lymph node positivity, and grade III histology were associated with an elevated risk of recurrence. Multivariate analysis further confirmed tumor T stage and lymph node metastasis count as significant risk factors for both disease-free survival and overall survival, with larger tumors and positive lymph node status linked to an increased risk of mortality. Conclusion NSM demonstrated oncological safety in this patient population. Prognostic factors significantly affecting survival outcomes included tumor T stage, lymph node metastasis count, and histological grade.